A passive low‐frequency seismic experiment in the Albertine Graben, Uganda. (5th July 2012) - Martini, F.; Lokmer, I.; Jonsdottir, K.; De Barros, L.; Möllhoff, M.; Bean, C. J.; Hauser, F.; Doherty, J.; Ryan, C.; Mongan, J.
ABSTRACT: A passive seismic experiment was conducted in April/May 2010 in the Albertine Graben region in Uganda to record low‐frequency seismic signals and explore the possibility of their exploitation in this area as a direct hydrocarbon indicator (DHI). Recordings were made at locations directly overlying both hydrocarbon and water‐bearing strata within the sedimentary basin as well as reference sites external to the basin, directly on the basement. Contrary to findings published in some literature to date, we found that spatial variations in the analysed wavefield parameters correlate with the underlying geology rather than the presence or absence of hydrocarbons. Inversion of the surface‐wave (fundamental mode) dispersion curve as well as the observed horizontal‐to‐vertical spectral ratio of both surface and body waves provide evidence that the observed spectral variations can be explained solely by a simple layered/gradient velocity model, without the presence of any kind of anomaly that could be attributed exclusively to a hydrocarbon reservoir. Consequently, it is recommended that knowledge of the geological and velocity structure is sought when analysing passive low‐frequency seismic data sets. This is a fundamental prerequisite in order to guard against misinterpretation of the spatial variation of seismic derived attributes as DHIs.